الخيانة الزوجية وآثارها الفقهية - مناني, نورالدین (Universty of Eloued جامعة الشهيد حمة لخضرالوادي, 2020)
الملخص تعتبر الخيانة الزوجية أحد المواضـيع الـتي كثـر الكـلام حولهـا إعلاميـا واجتماعيـا لانتشـارها بسـبب تـوافر عـد جوانـب عـدة تتعلـق بالموضـوع؛ ّ ، لـذا جـاءت هـذه الدراسـة لتبـين ة عوامـل أسـهمت في ذلـك ّ سواء مـن جانـب الحقـوق و الواجبـات الـتي تتعلـق بـالزوجين والـتي حرصـت الشـريعة الإسـلامية والقـانون الجزائري عليها لتكوين أسرة متماسكة يسودها الحب والمودة والوفاء و الالتزام، ثم تبين معـنى الخيانـة في اللغة و في القرآن والسنة وفي اصطلاح فقهاء الشريعة وفقهاء القانون، كما تذكر الدراسة هذه مجموعة سـبب انتشـار هـذه الجريمـة في أوسـاط اتمـع المسـلم؛ ثم ّ تبين من الأسباب التي تتعلق بالرجل و بالمرأة ل تطرقـت إلى الوسـائل الـتي حرصـت الشـريعة الإسـلامية عليهـا للحيلولـة مـن الوقـوع في الجريمـة، كمـا تم التطرق إلى ذكر أنواع الخيانة الزوجية، كالخيانة بإفشاء الأسرار، و الخيانـة في المـال، و الخيانـة في العاطفـة والجسـد، وهـذه الأخـيرة بينـا فيهـا شـروط قيامهـا وتوافرهـا، والمتمثلـة في: حصـول الـوطء، وقيـام الرابطـة ّ الزوجيـة أثنـاء ارتكـاب الجريمـة، و تـوفر القصـد الجنـائي؛ أي تعمـد ارتكـاب جريمـة الخيانـة الزوجيـة، كمـا تطرقت الدراسة إلى وسائل الإثبات في الشريعة والقانون للأخذ بحـدوث وقـو ع جريمـة الخيانـة الزوجيـة، وتعتبر وسائل محدودة بـالنص ولا يجـوز للقاضـي أن يسـتخدم مـن الأدلـة والوسـائل الـتي تكـون بخـلاف ذلك. الدراســة الجــزء الأهــم و المتعلــق بالآثــار المترتبــة علــى الــزوجين حــال ارتكامــا جريمــة ّوضحت ثم ــ الخيانة الزوجية، سواء كانت الخيانة الزوجية في ذروا؛ وهي جريمة الزنا أو ما دون ذلك، وتتمثل تلك ْ الآثار في الآثار البدنية، دية ق والآثار الع ، والآثار المالية، فأما الأولى ففيها الـرجم، والتعزيـر، والتخفيـف َ مـن العقوبـة، وأمـا الثانيـة: ففيهـا فـك الرابطـة الزوجيـة إمـا بـالطلاق أو الخلـع والتطليـق، وفيـه كـذلك فقـدان الحضـانة واللعـان ونفـي النسـب وحرمـة المصـاهرة، أمـا الآثـار الأخـيرة ففيهـا سـقوط المهـر والمتعـة ونقض الصلح والتعويض عن الضرر. وانتهـت الدراسـة بخاتمـة تضـمنت أهـم النتـائج، والـتي منهـا تطبيـق مبـدأ المسـاو اة في ترتـب الآثـار الفقهية والقانونية على الزوج والزوجة عند ارتكاما لجريمة الخيانة الزوجية Summary Infidelity is considered one of the subjects that has been widely talked about in the media and socially due to its spread because of the availability of several factors that contributed to this. Therefore, this study came to identify several aspects related to the subject whether through the rights and duties of the spouses, which the Sharia and the Algerian law are keen to create a cohesive family of love, affection, loyalty and commitment. Then it shows the meaning of betrayal in the language, in the Koran and Sunna, and in the terminology of Sharia jurists and jurists. This study mentioned set of reasons that relate to man and woman to show the cause for the spread of this crime in the Muslim community. Then it mentioned the means that Sharia was keen in order to prevent from falling into it. It was also mentioned the types of infidelity, such as betrayal in revealing secrets, treachery in money, and treachery in passion and body, and the latter we have shown in it the conditions for its existence and availability, which are: Having intercourse, establishing marital bond during the commission of the crime and malice aforethought occurring, i.e. intentionally committing the crime of infidelity. The study indicated to the means of evidence in Sharia and law to take into account the occurrence of the crime of infidelity, and it is considered limited means by the text and the judge may not use the evidence and means that are otherwise. Then the study touched on the most important part related to the problem of the topic, which is the effects on the spouses when they committed the crime of infidelity, whether infidelity is at its peak which is the crime of adultery or something less, and these effects are in the physical effects, doctrinal effects, and financial effects. The first includes stoning, scolding and mitigation of penalty. The second contains the untying of the marital bond either by divorce or ‘alkhula’ (divorce in exchange for the wife's compensation for the husband) and divorce from the judge in favor of the wife, and in it also the loss of custody and ‘alliean’ (sworn allegation of adultery committed by one's spouse) and denying the lineage and marriage kinship inviolability, while the financial effects include the fall of dowry and ‘almota’ (fall of money or property given to a divorced woman), privation of reconciliation, and compensation for damage. The study also mentioned the aspects of compatibility and the difference between the Sharia and the Algerian law, and perhaps the most important point of the compatibility is equality between the spouses in reproach when committing the crime of infidelity.
دراسة مقارنة مع لقانون الجزائري
أطروحة دكتوراه تخصص: الشریعة والقانون في العلوم الإسلامية
Keywords: : الخيانة الزوجية- الفقهية – القانون الجزائري – الآثار- الحقوق – الواجبات: marital infidelity - jurisprudence - Algerian law - effects - rights - duties